Proposal Of Marketing Communication Strategy To Accelerate Adoption And Diffusion Process Of Gentle Birth - Sarastri, Pramudita; Purwanegara, Mustika Sufiati (The Indonesian Journal of Business Administration, 2012)
The number of birth will always increasing. Based on the results of Census 2010, population is increasing about 1.96 percent each year. With a population of 2, 39 million, each year is estimated to 62.617 babies born in the city of Bandung.The purpose of this study was to explore the insights of pregnant women in order to create a strategy to accelerate the adoption and diffusion process for the philosophy of Gentle Birth.This research technique is using qualitative methods that apply ethnography method which consists of in-depth interviews, netnography, and videography. The purpose of using this technique is to analyze psychographic of pregnant women to explore in depth insight. In-depth interviews and observations conducted in Bandung in April-July 2012, on the 12 (twelve) of the respondents with the criteria were pregnant and the second trimester. Netnography conducted on discussion forums on the Internet which consists of Mommies Daily and Gentle Birth for All and observing conversations in the forums labeled